The Role of Magnetic Resonance Enterography for Detection and Differentiation of Pediatric Inflammatory Bowel Diseases - Özge Yapıcı; Eda Almus (Genel Tıp Dergisi)
Background/Aims: Inflammatory bowel diseases (IBD) are of two types: Crohn’s disease (CD) and ulcerative colitis (UC). The differential diagnosis of these two diseases is important because their treatment strategies are different. The present study aimed to evaluate the Magnetic Resonance Enterography (MRE) findings of pediatric patients who were clinically diagnosed with CD or UC. Material and Method: The patients under the age of 18, who underwent MRE examination, were retrospectively screened. Fifty five of those patients, who were clinically diagnosed with CD or UC, were included in the study. Bowel wall thickening, mesenteric fat tissue changes and complications were evaluated, and the findings were recorded. The sensitivity and specificity of MRE in the diagnosis of CD and UC in IBD patients were calculated. Results: Three of the patients clinically diagnosed with CD (7.3%) and six patients who had UC (42.9%) had involvement from the rectum to the proximal colonic segments (continuous lesions). Of those diagnosed with CD, 11 (26.8%) had skip lesions. In patients with IBD, the sensitivity of MRE for the diagnosis of CD was 56.1% and the specifity was 100%. The sensitivity of MRE for the diagnosis of UC was 42.9% and the specificity was 90.2%. Conclusion: MRE is helpful to identify the signs and complications of inflammatory bowel diseases. Although MRE has low sensitivity to differentiate between CD or UC in pediatric patients, it may help with its high specificity rates.